Hepatic Abnormal Secretion of Apolipoprotein C3 Promotes Inflammation in Aortic Dissection - Xinghui Zhuang; Mohammad Zarif; Yue Shen; Zhaofeng Zhang; Jian He; Linfeng Xie; Qingsong Wu; Xinfan Lin; Keyuan Chen; Yue Tian; Yong Lin; Yuling Zhang; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Apolipoprotein C3 (apo C3) is primarily secreted by the liver and is involved in promoting sterile inflammation and organ damage under pathological conditions. Previous studies have shown that apo C3 is abundant in the plasma exosomes of patients with aortic dissection (AD), but its specific role in AD remains unclear. Methods and Results In vivo, adeno‐associated virus was used to knock down hepatic apo C3 expression in an AD mouse model to assess the impact of liver‐derived apo C3 on the development of AD. In vitro, recombinant apo C3 protein was added to the culture medium of J774A.1 macrophages to evaluate its effect on macrophage polarization and to identify the underlying mechanisms. Additionally, the effect of apo C3 on the function of aortic endothelial and smooth muscle cells was explored. Apo C3 in the aortas of AD mice was found to originate from abnormal hepatic secretion, which enters the bloodstream and subsequently deposits in the aorta. Adeno‐associated virus–mediated hepatic apo C3 knockdown significantly reduced AD incidence (P=0.0036), macrophage infiltration (P=0.0004), and collagen deposition in the aorta (P=0.0016). Similarly, inhibiting the apo C3 receptor Toll‐like receptor 2 significantly lowered AD incidence (P=0.0352). In vitro, recombinant apo C3 protein promoted M1 polarization and matrix metalloproteinase secretion in macrophages by activating the Toll‐like receptor 2/NLR family pyrin domain containing 3 pathway. Additionally, apo C3 increased adhesion molecule expression in endothelial cells and induced inflammation, chemotaxis, and apoptosis in vascular smooth muscle cells. Conclusions Our findings highlight the role of abnormally secreted hepatic apo C3 in promoting aortic inflammation.